Pengurangan Jumlah Produk Setengah Jadi di PT. SEMB-PEL - Setiawan, Rizal; Widyadana, I Gede Agus; Palit, Herry Christian (Jurnal Titra, 2014)
The need for work in process on PCBA production line can be caused by fluctuating demand for PCBA products. Amount of work in process on production line that company wanted is between 3 up to 7 inventory days. Average current amount of work in process before implementation of proposed improvement is 12.03 inventory days. Root causes anaylise uses root cause tree. There are two proposed improvements, which are improvement on work in process updateâs system and improvement on material distribution to every work station. Proposed improvement that can be implemented is improvement on material distribution of every work station. Average amount of work in process after implementation the improvement is 6.72 inventory days.